2016
DOI: 10.1111/lam.12619
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity and biochemical characteristics ofBorassus akeassiiwine

Abstract: Our results highlight the evolution of palm wine during the 10 days separating palm tapping and consumption of the fermented wine. The fermentation step is performed within few hours and completed after 24 h. The next days, its acidity increases progressively with the production of lactic and acetic acids by bacteria. The high production of acetic acid is very likely one of the main cause of palm wine degradation during this period. This indicates that the solution to palm wine preservation might be protection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Results showed that the bacteria were significantly positively correlated with citric acid, ethanol, and acetic acid but negatively correlated with sugar content. In addition, acetic acid and lactic acid production was correlated with Lactobacillus , and the increase in acidity was apparently correlated with the abundance of Acetobacter , a result that was consistent with that of previous studies ( Papalexandratou et al, 2013 ; Tapsoba et al, 2016 ; Gammacurta et al, 2018 ). Correlation analysis revealed that Acetobacter was strongly correlated with acetic acid possibly because the pathway of acetic acid production was enhanced by Acetobacter in Nanfeng tangerine wine fermentation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Results showed that the bacteria were significantly positively correlated with citric acid, ethanol, and acetic acid but negatively correlated with sugar content. In addition, acetic acid and lactic acid production was correlated with Lactobacillus , and the increase in acidity was apparently correlated with the abundance of Acetobacter , a result that was consistent with that of previous studies ( Papalexandratou et al, 2013 ; Tapsoba et al, 2016 ; Gammacurta et al, 2018 ). Correlation analysis revealed that Acetobacter was strongly correlated with acetic acid possibly because the pathway of acetic acid production was enhanced by Acetobacter in Nanfeng tangerine wine fermentation.…”
Section: Discussionsupporting
confidence: 91%
“…Understanding the diversity and evolution of microorganisms during fruit wine fermentation is essential for controlling its production. Recent studies focused on the microbial composition and diversity during the wine fermentation based on culture-dependent methods ( Ghosh et al, 2015 ; Liu R. et al, 2015 ) or culture-independent methods ( Portillo and Mas, 2016 ; Tapsoba et al, 2016 ; Wei et al, 2018 ). These diverse microbial populations and their potential interplay in the different stages of alcoholic fermentation constitute a complex biological process that contributes largely to the final chemical composition ( Gammacurta et al, 2017 ) of wine and, therefore, to its sensory properties ( Hu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 26 samples, 120 morphologically different LAB were identified based on differential growth and in vitro probiotic characteristics. Previous studies have specified the presence of various LAB, non-LAB, and yeast in palm wine ( Tapsoba et al, 2016 ; Astudillo-Melgar et al, 2019 ). In our preliminary studies, it was observed that LAB were more abundant than non-LAB and yeasts in TPN.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no evidence that hazard analysis and critical control points (HACCP), a systematic preventive approach to food safety from biological, chemical, and physical hazards, are used during the production of palm wine among local processors. Many workers [7][8][9] have studied the microbial and biochemical constituents of the drink, especially compounds of microbial fermentation, and they are not currently regarded as hazards.…”
Section: Introductionmentioning
confidence: 99%